THE EFFECT OF CAPITAL STRUCTURE, CORPORATE GOVERNANCE, LIQUIDITY AND FIRM SIZE ON FIRM VALUE WITH ROE AS INTERVENING VARIABLES - Faridhatun Faidah (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2018)
This research is aim to analyze the factors that affect value of firms with ROE as a mediationvariable. Of 101 manufacture companies listed in Indonesian Stock Exchange during 2011-2015period are used as sample in this research. By using panel data regression and path analysisit is found that ROE is mediating the effect of DER to firm value. However, the mediating effectof ROE on institutional ownership, the current ratio and firm size to firm value are not founded.With this result it is suggested that to increase firm value companies should increase DER,institutional ownership and ROE.Keywords: Capital Structure, Corporate Governance, Liquidity, Firm Size, ROE, Firm Value